2012
DOI: 10.3184/095422912x13404690516133
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and cadmium in the marine macroalgae (Porphyra yezoensis and Laminaria Japonica) — forms and concentrations

Abstract: Total arsenic, inorganic arsenic (iAs), total cadmium concentrations and chemical forms of cadmium were analysed in Porphyra yezoensis collected monthly from January to April in 2011 and in Laminaria Japonica collected monthly from March to July in 2010. Results showed that total As concentrations in P. yezoensis were much lower than those in L. Japonica. The iAs concentrations in both macroalgae were all below the maximum limit according to the legislation in China, while total Cd concentrations in all sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
3
8
2
Order By: Relevance
“…The total arsenic in the L. japonica of our study was 61.100 ± 3.110 mg/kg, a slightly higher value than the 30–54 mg/kg reported by [ 27 ]. It is believed that the seaweed accumulates arsenic from seawater and the arsenic concentration in the seaweed is related to the environmental conditions, growth, and metabolic rate [ 27 ].…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…The total arsenic in the L. japonica of our study was 61.100 ± 3.110 mg/kg, a slightly higher value than the 30–54 mg/kg reported by [ 27 ]. It is believed that the seaweed accumulates arsenic from seawater and the arsenic concentration in the seaweed is related to the environmental conditions, growth, and metabolic rate [ 27 ].…”
Section: Resultscontrasting
confidence: 71%
“…The total arsenic in the L. japonica of our study was 61.100 ± 3.110 mg/kg, a slightly higher value than the 30–54 mg/kg reported by [ 27 ]. It is believed that the seaweed accumulates arsenic from seawater and the arsenic concentration in the seaweed is related to the environmental conditions, growth, and metabolic rate [ 27 ]. According to the LC-ICP-MS results, the concentrations of the species of arsenic in L. japonica were as follows: AsB (34.31 ± 1.21 mg/kg) > MMA (9.27 ± 0.96 mg/kg) > DMA (9.23 ± 0.83 mg/kg) > AsC (59.00 ± 1.65 mg/kg).…”
Section: Resultscontrasting
confidence: 71%
“…For example, the largest portion of Cd accumulated in roots and shoots of cabbage was found to be integrated with proteins and pectates (extracted by 1 M NaCl; Qiu et al ). Similar findings were reported as well for Porphyra yezoensis and Laminaria japonica (Zhao et al ). In addition, Wu et al () found that Cd‐resistant barley genotypes had higher concentrations of pectate‐ and protein‐integrated Cd and lower concentrations of Cd in water‐soluble and inorganic forms, compared with Cd‐sensitive genotypes.…”
Section: Discussionsupporting
confidence: 90%
“…As previously mentioned, the inorganic form of arsenic is the more toxic and speciation studies have shown that the predominant form of arsenic in algae is the organic . In addition, many algae are able to metabolize inorganic arsenic into organic forms …”
Section: Resultsmentioning
confidence: 96%
“…58 In addition, many algae are able to metabolize inorganic arsenic into organic forms. 59 In conclusion, the total composition of the red algae species P. palmata makes it the best candidate for utilization in food and feed. At the other end, the species least suitable for utilization seems to be the green alga C. rupestris.…”
Section: Ash and Mineral Contentmentioning
confidence: 99%